KELAYAKAN FINANSIAL DAN NILAI TAMBAH AGROINDUSTRI TAHU DI DESA BUKIT PENINJAUAN 1 KECAMATAN SUKARAJA KABUPATEN SELUMA - Sarina Sarina; Ikhsan Hasibuan (University of Prof. Dr. Hazairin, SH, 2021)
One of the essential sub-sectors that should develop to support the agricultural sector is the post-harvest agro-industry. Sederhana is the largest tofu factory in Bukit Peninjauan I village. The factory produces tofu daily to fulfill two traditional markets in Bengkulu City. This study aimed to evaluate the production cost, profit, income, R/C ratio, and added value at every production process. The study had been carried out in the Sederhana tofu factory in Bukit Peninjauan I village, Sukaraja sub-district, Seluma District, Bengkulu Province in November 2020. The data used in this paper were both primer and secondary data. The business qualification was determined by analyzing total cost, profit, income, R/C ratio, and added value. The results of this research showed that the Sederhana tofu factory had good quality business qualifications. For every 400 kg of soybean per production per day, it needed the total cost of Rp. 5,381,056.82. Meanwhile, the profit was about Rp. 6,600,000, and the income reached Rp. 1,218,943.18. Thus, the R/C ratio was 1.23 which was profitable. Besides, the added value was Rp. 6,433.34 per kg of soybean. However, the added value was the gross value since it contained labor income and share.